Is the bottom line reached? An exploration of supervisor bottom-line mentality, team performance avoidance goal orientation and team performance. (February 2022) - Lin, Yuying; Yang, Mengxi; Quade, Matthew J; Chen, Wansi
How do supervisors who treat the bottom line as more important than anything else influence team success? Drawing from social information processing theory, we explore how and when supervisor bottom-line mentality (i.e. an exclusive focus on bottom-line outcomes at the expense of other priorities) exerts influence on the bottom-line itself, in the form of team performance. We argue that a supervisor's bottom-line mentality provides significant social cues for the team that securing bottom-line objectives is of sole importance, which stimulates team performance avoidance goal orientation, and thus decreases team performance. Further, we argue performing tension (i.e. tension between contradictory needs, demands, and goals), serving as team members' mutual perception of the confusing environment, will strengthen the indirect negative relationship between supervisor bottom-line mentality and team performance through team performance avoidance goal orientation. We conduct a path analysis using data from 258 teams in a Chinese food-chain company, which provides support for our hypotheses. Overall, our findings suggest that supervisor's exclusive focus on the bottom-line can serve to impede team performance. Theoretical contributions and practical implications are discussed.